Achieving Lives Through The Secret Of Prayer - Nurhadi Nurhadi (Al-Mutharahah: Jurnal Penelitian dan Kajian Sosial Keagamaan, 2021)
The Prayer Application Reaps Wisdom in fetching your dreams is Prayer Early Time. Prayers at the beginning of time show the level of faith, piety, and love for Allah. Congregational Prayers at the Mosque. Prayers in the congregation are prayers performed by two or more people together. Prayers that are established in congregation reap benefits from the viewpoint of mathematics and economics, because they have multiple merit values, especially if they are performed in mosques that get 27 degrees. The Wisdom of Prayer Reaping Blessings is that Rawatib circumcision prayer is jewelry. The wisdom of the 24 cycles of rawatib prayer if it is carried out continuously or for eternity istiqomah it will become a piece of jewelry for a person in the hereafter, it will become a jewelry on the face that carries out namely the emanation of faith and obedience Dhuha Prayer is Wealth is a sunnah prayer to seek and ask for sustenance. Tahajjud prayer is tranquility, because of the business of a believer, it sends a servant away and lulled by intimacy with Allah in the clear silence of the middle of the night so that I get peace and serenity. Witir Prayer is Life because Witir Prayer is a right (life), so people who want to do it will get the right, every servant has the right to perform Witir prayer as much as he likes. One rak'ah, three, five, seven, nine, and eleven. So if a servant exercises his right, namely witir prayer, then he has the right to get his right to life.